1995
DOI: 10.1111/j.1365-2214.1995.tb00408.x
|View full text |Cite
|
Sign up to set email alerts
|

Parents' attributions about childhood cancer: implications for relationships with medical staff

Abstract: Improvements in therapy have resulted in increasing numbers of children being successfully treated for cancer. However, the aggressiveness of therapy and uncertainty about prognosis are associated with many adverse effects, psychological as well as physical, for both the child and family. This study investigates family coping with treatment in relation to attributions about cause and responsibility for onset of the disease. We interviewed parents of 30 children with cancer (28 mothers and 23 fathers) about the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 9 publications
1
22
0
2
Order By: Relevance
“…Bearison et al [7] found that internal types of attribution, and especially self-blame were reported most often. Eiser et al [18] also found self-blame to be a common attribution for mothers. Fathers were more likely than mothers to accept that there was no reason for the child's illness [18].…”
Section: Search For Meaningmentioning
confidence: 96%
See 1 more Smart Citation
“…Bearison et al [7] found that internal types of attribution, and especially self-blame were reported most often. Eiser et al [18] also found self-blame to be a common attribution for mothers. Fathers were more likely than mothers to accept that there was no reason for the child's illness [18].…”
Section: Search For Meaningmentioning
confidence: 96%
“…Communication with the medical staff is one of the three scales of the CHIP. Brown et al [10] found that parents often relied on understanding the medical situation through communication with the medical staff, while Eiser et al [18] found the contrary. They found that both mothers and fathers gave much lower ratings to the helpfulness of social support/information compared with the other three strategies measured with the CHIP.…”
Section: Communicationmentioning
confidence: 99%
“…21 It partly depends on the way children experience the treatment and its physical effects, 22 but also on the way their parents cope with this situation, 4 and on the quality of the staff-parentspatient relation. 23,24 However, the parents' confidence and ability to cope are also linked to their capacity to understand the doctors' explanations, which is also linked to their ambivalence towards them and towards the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Na literatura internacional sobre estratégias de enfrentamento adotadas por cuidadores em contexto onco-hematológico pediátrico, uma parte dos estudos focaliza a investigação de estratégias por meio do relato dos pais (Beltrão & cols., 2007;Goldbeck, 1998;Greening & Stoppelbein, 2007;Herman, 2007;Holm, Patterson & Gurney, 2003;James & cols., 2002;Munet-Vilaró, 1984;Norberg & cols., 2005;Patistea, 2005;Patistea, Makrodimitri & Pantelli, 2000;Rodrigues, Rosa, Moura & Baptista, 2000), enquanto outros trabalhos focalizam os processos psicológicos indicativos das estratégias de enfrentamento (Clarke-Steffen, 1997;Eiser, Havertnans & Elser, 1995;Elkin & cols., 2007;Enskär, Carlsson, Golsäter, Hamrin & Kreuger, 1997;Felder-Puig, Gallo, Waldenmair, Gadner & Topf, 2004;Hoekstra--Weebers, Jaspers, Kamps & Klip, 1998;Klassen & cols., 2007;Sloper, 2000;Steele, Long, Reddy, Luhr & Phipps, 2003;Tarr & Pickler, 1999;Trask & cols., 2003). Os principais resultados de ambos os tipos de estudo serão descritos a seguir.…”
Section: Enfrentamento: Caracterização E Mensuraçãounclassified
“…Algumas pesquisas indicam o uso intenso de estratégias de enfrentamento focalizadas no problema ou manejo do estressor, que envolvem busca por informações sobre doença e tratamento, controle da medicação e procedimentos médicos, vigilância sobre o estado de saúde da criança, planejamento de metas, cumprimento de recomendações médicas, redefinição cognitiva do problema (por exemplo, comparar a situações piores), organização da rotina, comunicação com a equipe, reorganização de papéis familiares, explicações à criança sobre o tratamento, conformação com a doença e negociações com a equipe médica (Clarke--Steffen, 1997;Eiser, Havertnans & Elser, 1995;Enskär, Carlsson, Golsäter, Hamrin & Kreuger, 1997;Goldbeck, 1998;Greening & Stoppelbein, 2007;Holm, Patterson & Gurney, 2003;James & cols., 2002;Munet-Vilaró, 1984;Norberg & cols., 2005;Patistea, 2005;Rodrigues, Rosa, Moura & Baptista, 2000;Steele, Long, Reddy, Luhr & Phipps, 2003;Tarr & Pickler, 1999;Trask & cols., 2003).…”
Section: Enfrentamento: Caracterização E Mensuraçãounclassified